2013
DOI: 10.1002/ajim.22231
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chemical exposure on cancer mortality in a French cohort of uranium processing workers

Abstract: Based on our pilot study, it seemed important to take into account chemical exposures in the analyses of cancer mortality among French uranium processing workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Two reports on a cohort of aerospace workers showed workers with a greater hydrazine exposure had an increased risk of death from lung cancer (RR = 1.45;95% CI:0.81–2.39), but that the increased risks were not statistically significant and the upper 95% confidence interval excluded a relative risk of more than 3 [ 6 7 ] An earlier study on the same cohort [ 8 ], had found a significant effect, but they had assumed all test stand mechanics were exposed to hydrazine, in the later studies they used a more precise exposure assessment [ 7 ]. A recent study of a French cohort of uranium processing workers also showed a non-significant increased risk of mortality from lung cancer after exposure to hydrazine (RR = 1.21; 95% CI: 0.68–2.17) [ 9 ], Both of these results are not inconsistent with our results.…”
Section: Discussionsupporting
confidence: 74%
“…Two reports on a cohort of aerospace workers showed workers with a greater hydrazine exposure had an increased risk of death from lung cancer (RR = 1.45;95% CI:0.81–2.39), but that the increased risks were not statistically significant and the upper 95% confidence interval excluded a relative risk of more than 3 [ 6 7 ] An earlier study on the same cohort [ 8 ], had found a significant effect, but they had assumed all test stand mechanics were exposed to hydrazine, in the later studies they used a more precise exposure assessment [ 7 ]. A recent study of a French cohort of uranium processing workers also showed a non-significant increased risk of mortality from lung cancer after exposure to hydrazine (RR = 1.21; 95% CI: 0.68–2.17) [ 9 ], Both of these results are not inconsistent with our results.…”
Section: Discussionsupporting
confidence: 74%
“…For example, TCE, as a chlorinated solvent, is a known carcinogen of group 1 according to the International Agency for Research on Cancer (IARC) 23. This exposure was not statistically significantly associated with excess lung and lymphohaematopoietic cancer as observed in our previous study 9. Finally, models were not adjusted for non-radiological exposures, because their simultaneous inclusion in the models produced unstable risk estimates.…”
Section: Discussionmentioning
confidence: 69%
“…Together with ionising radiation, uranium enrichment workers are known to be exposed to numerous non-radiological hazards 9 17 26. While these chemical and physical hazards are present in nuclear fuel cycle activities, they are rarely considered in epidemiological studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the risk of developing lung cancer increases in the cases with pre-existing nonmalignant lung deceases such as chronical obstructive lung decease, idiopatic lung fibrose and tuberculosis. A pilot sudy concerning the exposure to the chemical agents in French workers (28) confirms that the exposure to the risk factors multiplies the morbidity caused by lung cancer. The difference in professional distribution in both groups in this study, concerning the health status, was not high enough to be statistically verified.…”
Section: Discussionmentioning
confidence: 86%